1998
DOI: 10.1063/1.166333
|View full text |Cite
|
Sign up to set email alerts
|

The effect of convection on a propagating front with a liquid product: Comparison of theory and experiments

Abstract: This work is devoted to the investigation of propagating polymerization fronts converting a liquid monomer into a liquid polymer. We consider a simplified mathematical model which consists of the heat equation and equation for the depth of conversion for one-step chemical reaction and of the Navier-Stokes equations under the Boussinesq approximation. We fulfill the linear stability analysis of the stationary propagating front and find conditions of convective and thermal instabilities. We show that convection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 35 publications
1
32
1
Order By: Relevance
“…McCaughey et al tested the analysis of Garbey et al and found the same bifurcation sequence of antisymmetric to axisymmetric convection in ascending fronts [83] as seen with the liquid/solid case.…”
Section: CMmentioning
confidence: 99%
“…McCaughey et al tested the analysis of Garbey et al and found the same bifurcation sequence of antisymmetric to axisymmetric convection in ascending fronts [83] as seen with the liquid/solid case.…”
Section: CMmentioning
confidence: 99%
“…[19] A great deal of attention has also been devoted to the instability of polymerization fronts. The studies focused on linear stability analyses, [20,21] convective instabilities, [22,23] and nonlinear dynamics of polymerization waves. [24][25][26][27] Mathematical models of frontal free-radical polymerization were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The opposite is the case for other families of reactions 14 such as the chlorite-tetrathionate ͑CT͒, [15][16][17][18][19][20][21][22][23] nitric acid-iron͑II͒, [24][25][26] reactions, or polymerization fronts. 50,51 Here, in isothermal conditions, the reaction products are denser and so a downward propagating front will be buoyantly unstable featuring density fingering while the upward moving front remains stable. An alternative way for reaction-diffusion fronts to become unstable is through the diffusion coefficients of the substrate and autocatalyst being sufficiently different.…”
Section: Introductionmentioning
confidence: 99%